(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The Indian rural market is becoming lucrative and demanding both for the companies and the customers. It is filled with challenges and opportunities both. On one hand, there are specific characteristics of the rural market which stops the companies to enter and perform on the other hand the market invites great business volumes in terms of population and its uniqueness.